From 3 R's to 3 C's: Corporate Curriculum And Culture in Public Schools - Mahiri, Jabari (Social justice, 2005)
Part of a special issue on challenging corporate control of schools and communities. The writer discusses the current extent of collusion between corporations, banks, and governments with regard to public education in the U.S. in the quest to maximize profits. He argues that textbook corporations that promote scripted curriculums linked to standardized tests contribute to the process of ensuring support for U.S. commercial and political interests. Noting that teachers, students, parents, and community members are now fighting this form of corporate takeover and control of public schools, he charts the struggle of one such group, the Alliance for Meaningful Education in northern California's West Contra Costa Unified School District.